2018
DOI: 10.3390/su10103431
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Consumption of Bottled Water at the University of the Basque Country: Showcasing Tap Water as the Real Alternative towards a Water-Sustainable University

Abstract: This paper examines the beliefs and environmental attitudes of university individuals towards bottled and tap water use and examines tap and bottled water availability and sales volumes at the University of the Basque Country. The research employed a mixed methods approach including (i) an exploratory survey to document environmental beliefs and behaviors towards bottled and tap water; (ii) written questionnaires addressed to faculty administrators to inquire about accessibility to tap water and, (iii) persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…The most drastic move to promote tap water would be to impede access to bottled water. Some municipal and regional governments (in Australia, Canada, Hong Kong, and the United States) have instituted bans on the commercialization of bottled water in the public sphere (Díez, Antigüedad, Agirre, & Rico, ). For example, the government of the Canadian provinces of Manitoba and Nova Scotia have banned bottled water in provincially owned facilities (Pacheco‐Vega, ).…”
Section: Assessment Of the Commission's Strategies In Light Of The LImentioning
confidence: 99%
See 1 more Smart Citation
“…The most drastic move to promote tap water would be to impede access to bottled water. Some municipal and regional governments (in Australia, Canada, Hong Kong, and the United States) have instituted bans on the commercialization of bottled water in the public sphere (Díez, Antigüedad, Agirre, & Rico, ). For example, the government of the Canadian provinces of Manitoba and Nova Scotia have banned bottled water in provincially owned facilities (Pacheco‐Vega, ).…”
Section: Assessment Of the Commission's Strategies In Light Of The LImentioning
confidence: 99%
“…The third strategy used by the European Commission and some national initiatives on tap water focuses on elucidating the positive health, environmental, and social impacts of tap water use (see, e.g., Goggins & Rau, ; Wilk, ). Business studies and research in economics have stressed the positive impact of switching from bottled water to tap water for protecting the climate and the environment (see, e.g., Díez et al, ; Hawkins, ). For example, Torretta () alludes to the resources and energy needed to produce the plastic for bottled water as well as to the carbon dioxide emissions resulting from the transportation of bottled water.…”
Section: Assessment Of the Commission's Strategies In Light Of The LImentioning
confidence: 99%
“…HLW aimed to reduce plastic bottle litter by providing an alternative source of cold water in an area where plastic bottle litter accumulates, rather than in an area of bottled water purchases. Hence, the current location of the Go2Zones is likely providing water to consumers who already have cold water, whether it be in a reusable bottle or a single-use plastic water bottle [23,51]. For the Go2Zones to maximise their impact as an intervention opportunity, they may be better placed where consumers purchase bottled water, which is the main point of bottled water supply and demand.…”
Section: Location Location Locationmentioning
confidence: 99%
“…In Australia, bottled water is predicted to be the fastest growth sector in the beverage industry [20] with Australians spending more than half a billion dollars per year on bottled water [21]. This increased consumption has been linked to the preconception by consumers that bottled water is healthier, more convenient, and tastier than tap water [21][22][23]. That rationale is illusionary, however [24], with tap water often demonstrated to be 'cleaner' or less contaminated than that sold in bottles.…”
Section: Introductionmentioning
confidence: 99%
“…Wilk [13] (p. 303) understands this development from a cultural perspective and describes it as a case where sound cultural logic leads to environmentally destructive behavior. A range of factors have already been identified that have an effect on public perception of drinking water quality [14] and bottled water [15] such as sociodemographics and implicit and explicit attitudes [16,17], consumers' perceptions [12,18] and behavior [19].…”
Section: Introductionmentioning
confidence: 99%